Proceedings of the 23rd ACM International Conference on Conference on Information and Knowledge Management 2014
DOI: 10.1145/2661829.2662077
|View full text |Cite
|
Sign up to set email alerts
|

Sketch-based Influence Maximization and Computation

Abstract: Propagation of contagion through networks is a fundamental process. It is used to model the spread of information, influence, or a viral infection. Diffusion patterns can be specified by a probabilistic model, such as Independent Cascade (IC), or captured by a set of representative traces.Basic computational problems in the study of diffusion are influence queries (determining the potency of a specified seed set of nodes) and Influence Maximization (identifying the most influential seed set of a given size). A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
205
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(208 citation statements)
references
References 26 publications
2
205
0
1
Order By: Relevance
“…• Constant model: All the edges has the same constant probability p as in [6,8,17]. We consider three di erent values of p, i.e.…”
Section: Experimental Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Constant model: All the edges has the same constant probability p as in [6,8,17]. We consider three di erent values of p, i.e.…”
Section: Experimental Settingsmentioning
confidence: 99%
“…Most of the existing work in network cascades uses stochastic diffusion models and estimates the in uence spread through sampling [8,11,17,23,29,31]. The common practice is to use a xed number of samples, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can quite efficiently calculate the bottom-k sketch of each node in the network by orderly assigning the rank values from the smallest one to those nodes reachable by reversely following links over the network. Based on this framework, a greedy Sketch-based Influence Maximization (SKIM) algorithm has been proposed, and it has been shown that the SKIM algorithm scales to graphs with billions of edges, with one to two orders of magnitude speedup over the best greedy methods [13]. Thus, we also develop our method of detecting critical links under the framework of the bottom-k sketching algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Here, we used the same random value r(v) assignment for each trial so that the bottom-k sketches of all the nodes are the same for any method, i.e., it is guaranteed that each method can produce the same result. Figure 1 shows the computation times of each method for five trials plotted by dots and the average values over these trials plotted by different markers as indicated in the figure, where we set k = 64 for calculation of the bottom-k sketches of all the nodes according to [13]. Figure 1(a) compares the actual processing times of these methods, where our programs implemented in C were executed on a computer system equipped with two Xeon X5690 3.47GHz CPUs and a 192GB main memory with a single thread within the memory capacity.…”
Section: Computational Efficiencymentioning
confidence: 99%